THE MACROSEMIIDAE (PISCES, ACTINOPTERYGII) FROM THE UPPER TRIASSIC OF LOMBARDY (N. ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
A new species of Macrosemiid, Legnonotus obtusus sp. n. from Carnian aged rocks near Varese, Lombardy, Italy, is briefly described and a redescription given of the species Legnonotus krambergeri Bartram based on new material from the Upper Norian beds of the Prealps near Bergamo. It is concluded that Legnonotus is a primitive Macrosemiid.
Keywords: Macrosemiidae (Pisces, Actinopterygii); Upper Triassic; Lombardy (N. Italy); redescription; new taxon.